SAMARQAND VILOYATI G‘O‘ZA AGROTSENOZLARIDA G‘O‘ZA TUNLAMI RIVOJLANISHIGA ENTOMOFAGLARNING TA’SIRINI O‘RGANISH - Fayzullaev B., Fayzullaev B.; Abdumalikov J.Q., Abdumalikov J.Q. (Actual problems and prospects of the study of the fauna, 2024)
This article provides data on the study of the developmental phase of the cotton bollworm. The effectiveness of the use of a biological method of combating this pest in cotton agrocenoses in the conditions of the Samarkand region was studied. Methods for using a pheromone trap to combat cotton bollworm were studied and showed high technical efficiency.